DOES THE “OBESITY PARADOX” REALLY TAKE PLACE IN CORONARY HEART DISEASE? - O. M. Drapkina; R. N. Shepel; S. O. Eliashevich (Кардиоваскулярная терапия и профилактика, 2016)
The article is focused on clinical trials of the “obesity paradox” in patients with coronary heart disease.